APLIKASI DOSIS TRICHOKOMPOS JERAMI PADI PADA BIBIT KOPI ROBUSTA (Coffea canephora Pierre) - Eko, Satria; ', Sampoerno; ', Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Coffee is one of the plantation commodities which have economic value and play an important role as a source of foreign exchange. In order to improve the productivity it is required good seedling. Attempts  to increase coffee productivity are selection varieties, plant maintenance and appropiate fertilization. The use of organic fertilizer nutrients can contribute also further role in the process of decomposition of the soil organic matter. Organic fertilizer which can be used include paddy straw Trichokompost. Paddy straw Trichokompost rice is easy to apply, does not produce a poison (toxin), environmentally friendly and does not interfere with other organisms that benefit for plants, especially organisms in the soil. This study aims to determine the effect of various dosage paddy straw Trichokompost in Robusta coffee seedlings and get an appropriate dosage for seedling growth of Robusta coffee (Coffea canephora Pierre). The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau. This research was carried out for three months starting from March to June 2015. The study was conducted using a completely randomized design (CRD) with 5 treatments and 4 replications so that a total of 20 experiments units. Each unit consisted of 3 seedling thus obtained 60 seedling. Treatments were 0, 25, 50.75 and 100 g/plant. Parameters measured were the increase seedling height (cm), the number of leaves increase (pieces), addition girth (cm), leaf area (cm2), dry weight (g) and the ratio of the root crown. Statistical analysis using ANOVA and observation further analysis of significant variance with the Least Significant Difference at 5%. Application of paddy straw Trichokompost 75 g / plant (15 tonnes / ha) and the application of paddy straw Trichokompost 100 g / plant (20 tonnes / ha) gives the best coffee seedling growth in all parameters of robusta coffee seedling. Keywords: robusta coffee, paddy straw Trichokompost, seedling